(untitled) - Beverly Spears Blackmon (belmont, California, 1982)
The book guide you through the four basic phases of the writing process: thinking, drafting, re-thinking, anf writing. Get ready to discover the real satisfaction of learning how to focus on sound ideas, organize them clearly, develop them logically, and write them down so people understand what you mean to say
Keywords: english language - rhetoric